Religion and Politics in America's Borderlands - Azaransky, Sarah; Espín, Orlando O.; Nanko-Fernández, Carmen; Carroll R., M. Daniel; Machado, Daisy L.; Rios, Pedro; Maher, Monica A.; Wong, Craig; Fanestil, John; Méndez Montoya, Ángel F. (Lexington Books, 2013)
Religion and Politics in America's Borderlands brings together leading academic specialists on immigration and the borderlands, as well as nationally recognized grassroots activists, who reflect on their varied experiences of living, working, and teaching on the US-Mexico border and in the borderlands. Upper level undergraduate students, graduate theology and social science students, and the educated public would benefit from its incisive analysis of the ways the borderlands challenge conventional interpretations of Christianity.